The meaning and legal consequences of 'Sole-trustee' of Waqf under the shariah and Malaysian Waqf laws - Syed Abdul Kader, Sharifah Zubaidah; Ishola, Abdullahi Saliu; Mohamad, Nor Asiah (LexisNexis, 2018)
Malaysia has state level laws relating to waqf and all these laws contain a provision making the State Islamic Religious Council as 'sole trustee' of all waqf properties in their respective states. This effectively makes the State Islamic Religious Council as the sole waqf authority for the state. Problems have arisen in regard to the scope of powers of the State Islamic Religious Councils in exercising their powers as 'sole trustee' for waqf in Malaysia. With the aim of minimising these problems and seeking legal solutions, this article examines the meaning and legal consequences arising from the term 'sole trustee' in the context of waqf laws in Malaysia. It traces the rationale for inclusion of such provision and identifies some anomalies arising therefrom. The concepts of nazir, mutawalli and qayyim under the Shariah law are discussed, issues relating to delegation of powers, appointment of waqf managers, the function and duties of waqf managers are examined, and issues arising from decided cases are identified. Findings provide direction for the waqf authorities to act and strategise for waqf management and development in Malaysia in accordance with the parameters of the Shariah and the law.